2014
DOI: 10.1161/strokeaha.114.005626
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Calcification, Intima-Media Thickness, and Ankle-Brachial Index Are Complementary Stroke Predictors

Abstract: I n the population-based and prospective Heinz Nixdorf Recall (HNR) cohort, we have demonstrated previously that coronary artery calcification (CAC) determined by electronbeam computed tomography is a potent predictor of incident stroke in addition to established risk factors that are part of the Framingham risk score.1 In addition, we have shown that 2 markers of peripheral atherosclerosis, that is, intima-media thickness of the common carotid arteries (carotid intimamedia thickness [CIMT]) 2 and ankle-brachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…It has also been identified as a risk factor for coronary heart disease ( 2 ). Large vessel disease biomarkers such as atherosclerosis are linked to cerebrovascular disease ( 6 , 7 ) and have been extensively studied in migraine ( 8 10 ), but have not yet elucidated common mechanisms. Increasing evidence shows that microvascular pathology also contributes to stroke and coronary heart disease ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been identified as a risk factor for coronary heart disease ( 2 ). Large vessel disease biomarkers such as atherosclerosis are linked to cerebrovascular disease ( 6 , 7 ) and have been extensively studied in migraine ( 8 10 ), but have not yet elucidated common mechanisms. Increasing evidence shows that microvascular pathology also contributes to stroke and coronary heart disease ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“… 27 Another study conducted in the same population revealed that although coronary artery calcification scoring, CCA IMT and ankle‐brachial index provided complementary information, the ankle‐brachial index had the greatest predictive value on stroke risk. 28 In both studies, the overall predictive ability of the IMT was lower than that of the other 2 measures. 27 , 28 Similarly, the Multi‐Ethnic Study of Atherosclerosis showed that coronary artery calcification and carotid plaque improved predictions of coronary heart disease and stroke to a greater degree than did a large CCA IMT.…”
Section: Discussionmentioning
confidence: 73%
“…Combining CAC with other measures of subclinical atherosclerosis such as carotid IMT or plaque presence may be more promising for discriminating ischemic stroke/TIA. 3435, 36 Potentially, increased carotid artery IMT and the presence of carotid plaque are associated with intracranial atherosclerosis 37 , which is strongly associated with ischemic stroke/TIA. 38 However, carotid artery IMT has not been routinely recommended for atherosclerotic cardiovascular disease risk assessment due to a lack of sufficient evidence in the current guidelines.…”
Section: Discussionmentioning
confidence: 99%